2022
DOI: 10.1002/lpor.202200265
|View full text |Cite
|
Sign up to set email alerts
|

Toward High‐Efficiency Ultrahigh Numerical Aperture Freeform Metalens: From Vector Diffraction Theory to Topology Optimization

Abstract: Optical metasurface is a 2D array of subwavelength meta-atoms that arbitrarily manipulates amplitude, polarization, and wavefront of incident light, offering great advantages in miniaturization and integration. However, the presuppositions hidden in conventional unit-cell-based design approach, including discrete phase sampling, local periodicity approximation, and normal response, imply that the responses and interactions of meta-atoms are almost impossible to be accurately modeled, thus impeding the effectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
30
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 48 publications
0
30
0
Order By: Relevance
“…55 As shown in Figure 2b, Sang et al comprehensively investigated the efficiency gap between the conventional high numerical aperture (NA) metalens and the theoretical limitation of vector diffraction theory. 64 Moreover, Xu et al first introduced the topology optimization into disordered meta-optics and demonstrated that, with the efficient suppression of the lattice coupling effect, long-range ordered complex electric field could be realized in a disordered freeform metasurface (Figure 2c). 66 Although the computation complexity of topology optimization is relatively low, it is still a great challenge to inversely design a large-scale aperiodic metasurface because full-model rigorous electromagnetic simulation is required.…”
Section: ■ Intelligent Design Of Metasurfacesmentioning
confidence: 99%
See 2 more Smart Citations
“…55 As shown in Figure 2b, Sang et al comprehensively investigated the efficiency gap between the conventional high numerical aperture (NA) metalens and the theoretical limitation of vector diffraction theory. 64 Moreover, Xu et al first introduced the topology optimization into disordered meta-optics and demonstrated that, with the efficient suppression of the lattice coupling effect, long-range ordered complex electric field could be realized in a disordered freeform metasurface (Figure 2c). 66 Although the computation complexity of topology optimization is relatively low, it is still a great challenge to inversely design a large-scale aperiodic metasurface because full-model rigorous electromagnetic simulation is required.…”
Section: ■ Intelligent Design Of Metasurfacesmentioning
confidence: 99%
“…By imparting the abrupt phase shift at the interface, LC molecules with spatially variant orientations can be used to generate desired phase profiles based on the PB geometric phase. 84 fabrication resolution has also been developed to precisely control the orientations of LC molecules. The half-wave condition can be realized by controlling the thickness of the LC layer to achieve a high polarization conversion efficiency, up to 100% at the designed wavelength.…”
Section: Fabricationmentioning
confidence: 99%
See 1 more Smart Citation
“…where G is the total incident radiation, which can be expressed as 𝐺 = 𝐶 × 1000𝑊 ∕ 𝑚 2 [31], C is the solar concentrating coefficient, 𝜎 is the Stepan-Boltzmann constant and 𝜎 = 5.67 × 10 −8 𝑊 ∕ (𝑚 2 ⋅ 𝐾 4 ) , 𝑇 is the operating temperature of the absorber, 𝑇 0 is the atmospheric temperature which is agreed to be 273K. When C=1 and T=300K, the solar-thermal conversion efficiency 𝜂 of the proposed absorber is calculated to be 93.92%.…”
Section: (Red Line)mentioning
confidence: 99%
“…In addition to the basic performance of the traditional broadband absorber, solar absorber, as a kind of broadband absorber, is also required to have excellent spectral selectivity which is important to high absorption in solar spectra and low loss of thermal radiation emissivity in the mid-infrared band. With the deep research on metamaterial and surface plasmon, wideband absorbers with excellent spectral selectivity and insensitivity to polarization and incidence angle have been proposed one by one [3][4][5][6][7], which is expected to be applied in the design of solar absorbers. Further, kinds of solar spectrally selective absorber structures such as multilayer metal/insulator/metal structure [8][9][10][11][12], fishnet gratings [13][14][15][16], moth eye [17][18][19], and ring structure [20][21][22][23] have been studied for solar thermal absorption.…”
Section: Introductionmentioning
confidence: 99%